All Insignificant things Must Disappear. (1st August 2013) - Carrier, David
Although Trinity Church at Wall Street is within easy walking distance of Chelsea, the art to be found in the museum inside is traditional sculpture and mostly memorials to its privileged parishioners. But now, for the first time, this Episcopal Church has embraced an exhibit of contemporary art, called "All Insignificant Things Must Disappear." This small gallery was crammed full of art, none of it in fact dedicated to religion as such, but to the impact of the economic crises on artistic practice